IMPLEMENTASIKEBIJAKAN PENGADAAN BARANG DAN JASA PEMERINTAH DI DINAS PEKERJAAN UMUM KABUPATEN BUTON - Latief, Anwar (JI@P, 2015)
Anwar Latif, 2015. âImplementation of governmental product and serviceprovision policy in Public Work Service of Buton Regencyâ. Slamet RiyadiUniversity, Thesis, unpublshed.This research aimed were firstly to describe the implementation of governmentalproduct and service provision policy in Public Work Service of Buton Regency,and secondly to analyze the factors inhibiting the implementation of governmentalproduct and service provision policy in public sector in the Public Work Service ofButon Regency. The perspective employed in this study was descriptivequalitative using descriptive explorative approach. It means that this studydescribes and explored the so far undisclosed reality and then explained andapplied in order to get an actual description. The research model employed waspublic policy analysis framework referring to Van Meter and Van Hornâsperspective seeing that the implementation of policy is necessary to find out therelationship between policy implementation and other factors. The effectivenessof product and service procurement is the government attempt in meeting thepublic need. This research made an observation on policy substance(Presidential Regulation No.70 of 2012), resource and social-economic condition.The sample taken was consisted of: (1) the product and service provisioncommittee of Regencyâs Public Work Service, (2) contractor, and (3) Nongovernmentalorganization/society. The instruments used were: (1) in-depthinterview, aiming to guide and to facilitate the author in directing the interview,and (2) document study in order to confirm the result of interview with theinformant, particularly pertaining to the data of product and service provisionpolicy implementation in Buton Regencyâs Public Work Service. Result ofresearch suggested that the implementation of product and service provisionpolicy in Buton Regencyâs Public Work Service showed the less optimum result,as indicated by the less successfully provision of high-quality and useful facilityfor the public, and the discriminative process and mechanism. The inhibitingfactors in the implementation of product and service provision policy wereuncertain weather that influence the implementation of activity was sufficientlydistracted by uncertain weather condition and relatively short time of budgetchanging activity implementation.Keywords: policy Implementation, product and service provision, product and serviceprocurement.